The Relationship between Basic Sanitation of Healthy Homes and Personal Household Hygiene with the Incidence of Stunting in Toddlers in Residential Area around TPA Cipeucang in 2023 - Prima Gita Pradapaningrum; Haryoto Kusnoputranto (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: Stunting is one of the problems of malnutrition in toddlers in Indonesia. Environmental sanitation has an important role in stunting. Waste management that has not been maximized at the TPA can cause environmental sanitation pollution and a lack of clean living behavior. Cipeucang TPA is the only TPA for the South Tangerang area, with 2 Sub-Districts that are close to the TPA experiencing an increase in stunting cases in 2021-2022. This study aimed to determine the relationship between basic sanitation in a healthy home and personal hygiene households with the incidence of stunting in toddlers in the residential area around TPA Cipeucang. Methods: This type of research is observational analytic through a cross-sectional approach. The study population was all toddlers in settlements around the TPA covering 2 Sub-Districts with 4 RT and 2 RW. The research sample was 86 using a purposive sampling technique. The research was conducted from April to June 2023. Data analysis used univariate, bivariate (Chi-square test), and multivariate (logistic regression test). Results: The results showed that there was a relationship between drinking water facilities and stunting (p=0.05, POR=1.89), and became the dominant factor causing stunting (p=0.054). While clean water facilities (p=0.374, POR=1.44), latrines (p=0.613, POR=1.22), wastewater disposal facilities (p=1.000, POR=1.54), skin hygiene (p =1.000, POR=1.24) and hand and nail hygiene (p=0.625, POR=1.22) were not related to stunting but were risk factors for stunting. Waste management facilities (p=0.310) have no relationship with stunting and are not a risk factor. Conclusion: There is a relationship between drinking water facilities and the incidence of stunting in toddlers in the residential area around TPA Cipeucang.